Development of a Nomogram for Moderate-to-Severe Bronchopulmonary Dysplasia or Death: Role of N-Terminal Pro-brain Natriuretic Peptide as a Biomarker - Song, Min; Lei, Mengyuan; Luo, Chenghan; Shi, Zanyang; Cheng, Xinru; Ding, Wenqian; Cao, Wenjun; Zhang, Jingdi; Ge, Jian; Wang, Mengmeng; Xia, Peige; Mao, Fengxia; et al. (Frontiers in Pediatrics, 2021)
Objectives: This study aimed to explore the clinical value of N-terminal pro-brain natriuretic peptide (NT-proBNP) in predicting moderate-to-severe bronchopulmonary dysplasia (BPD)/death, and to establish an effective clinical predictive nomogram. Methods: We retrospectively analyzed very low birth weight infants (VLBWs) with gestational age≤32 weeks. The NT-proBNP values were determined on the 1st, 3rd, 7th, 14th, 21st and 28th days after birth. The correlation between NT-proBNP level and moderate-to-severe BPD/death was evaluated. Receiver operating characteristic (ROC) curve analysis was used to evaluate the prediction ability. Then, we used multivariable logistic regression to build the prediction model and nomogram, and calibration of the model was assessed by calibration curve. Results: In total, 556 VLBWs were involved, among whom 229 developed BPD (mild: n = 109; moderate: n = 68; severe: n = 52) and 18 died. The NT-proBNP level in the moderate-to-severe BPD/death group was significantly higher than that in the no-to-mild BPD group from the 3rd to 28th day (P＜0.001). When the natural logarithm of the serum NT-ProBNP level increased by 1 unit at day 7 (±2 days) of life, the risk of moderate and severe BPD/death was the highest (OR = 3.753; 95% CI: 2.984~4.720), and ROC analysis identified an optimal cutoff point of 3360 ng/L (sensitivity: 80.0%; specificity: 86.2%; AUC: 0.861). After adjusting for confounding factors, the level of NT-proBNP at day 7 (±2 days) of life still had important predictive value for the development of moderate-to-severe BPD/death, significantly improving the predictive ability of the model. Conclusion: The level of NT-proBNP at day 7 (±2 days) of life can be used as an early promising biomarker for VLBWs to develop moderate-to-severe BPD/death. We constructed an early predictive nomogram to help clinicians identify high-risk populations.